18F-FDG PET/CT of cervical carcinoma. - Patel, C; Nazir, SA; Khan, Z; Gleeson, F; Bradley, K (2011)
OBJECTIVE: This article outlines the role of FDG PET/CT in patients with cervical carcinoma for evaluating tumor extent, assessing treatment response, and detecting disease recurrence. CONCLUSION: There is increasing evidence that FDG PET/CT has a role in the primary evaluation of cervical carcinoma-in particular, for evaluating lymph node status and distant metastatic disease. PET/CT is also helpful to determine prognosis, assess treatment response, and evaluate disease recurrence.